(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article considers the theoretical principles of improving the design of membrane equipment for concentrating and purifying juices. The current state of membrane technologies is analyzed, the main problems of the operation of the devices are identified, and a design concept with turbulizing inserts is proposed, aimed at increasing the efficiency of mass transfer, reducing membrane contamination, and improving the energy efficiency of the process.